Study of Solar Energy Potential for Stirlng Engine Design (Case Study: Indramayu) - FARHAN CHAIRAHMAN (NIM: 12811034); Pembimbing: Dr. Plato Martuani Siregar, S.Si., M.Si., MUHAMMAD
Indramayu is located in Northen West Java which have relative good solar energy potential by insolation approximately 550 W/m2 hence could be a sample region which utilizing solar power in daily activity. The insolation value measured by Energy Balance Approach. Insolation affected by direct variables such Outgoing Longwave Radiation (OLR), Cloudiness, and Rainfall, also indirect variables such periodisity of El Nino Southern Oscillation (ENSO) and Lunar Position. Stirling engine able to use solar radiation heat to generate mechanical movement by temperature difference for cut-in reach to 100oC. The inlet temperature to the hot chamber of stirling engine measured from insolation in Indramayu. In this study, found that temperature which produced from insolation only cant generate the stirling engine. Thus, need a system design which can increasing incoming radiation to the engine and generate the engine even with absence of the sun. In this study found that Fresnel lens with optical efficiency 50.6% and Geometrical concentration ratio 62.64 times can multiply intensity of incoming radiation (insolation) 31.32 times. Usage of chemical storage system by Zeolite pellet and chemical reaction between Magnesium Sulphate (MgSO4) and Water (H2O) allow stirling engine to keep working even without main heat source from sun.